Strategi Humas Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional dalam Menciptakan Citra Positif Kementerian - Erman Anom; Ahmad Zamroni ‘Aziiz (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the strategy used by the Public Relations Ministry of ATR/BPN in publishing information through the scope of Public Relations to the public. This study uses a qualitative approach with a case study research method. The results showed that the Public Relations Communication Strategy in Enhancing the Positive Image of the Ministry of ATR/BPN in enhancing the positive image of the Ministry of ATR/BPN included internal and external strengthening by utilizing social media and conventional media in terms of building a positive image by using the momentum of handing over certificates from the results of the National Strategic Program . Keywords: Positive Image, Public Relations, Ministry of Agrarian Affairs